ANALISIS PUTUSAN HAKIM DALAM MENCARI PUTUSAN FORMIL - Lubis, Fauziah; Harahap, Fitri Hasanah; Ananda, Muhammad Rafly; Amanda, Mutia; Harahap, Raihan Fadila; Rambe, Sri Wulan (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This study discusses the practice of formal judgments (Niet Ontvankelijk Verklaard) in Indonesian civil procedural law, particularly when such decisions are issued due to formal defects in a lawsuit. In a civil law system that upholds the passive principle for judges, the authority to determine the scope of a case lies entirely in the hands of the parties involved. However, when this passive principle is rigidly applied, judges tend to issue formal judgments without considering the substance of the case, potentially neglecting substantive justice. This research aims to analyze the types of formal defects that lead to inadmissibility of lawsuits and evaluate the judicial approach in issuing formal decisions so as not to disadvantage justice seekers. The research employs a normative juridical method, with data collection conducted through literature study, using secondary data sources such as textbooks, scholarly articles, legal journals, and legislation. The analysis is carried out using a qualitative descriptive approach with a juridical perspective on the application of formal judgments in judicial practice. The findings indicate that formal judgments are relative in nature, as they only assess procedural aspects without touching upon the merits of the case. Therefore, such decisions do not eliminate the plaintiff’s right to refile the claim after necessary corrections. Judges are ideally expected to maintain neutrality while also acting wisely by allowing space for improvements in lawsuits, in order to uphold the principle that the administration of justice must be carried out fairly, with a simple process, expedited proceedings, and minimal costs, as stipulated in Article 2 paragraph (4) of Law Number 48 of 2009 concerning Judicial Power.